Adjusted D-dimer cutoff levels to rule out pulmonary embolism in patients hospitalized for COPD exacerbation: results from the SLICE trial - Rodríguez, Carmen; Jara-Palomares, Luis; Tabernero, Eva; Tenes, Andrés; González, Sara; Briceño, Winnifer; Lobo, José Luis; Morillo, Raquel; Bikdeli, Behnood; Jiménez, David (Thrombosis journal, 2022)
Background For patients with suspected pulmonary embolism (PE), age- or clinically-adjusted D-dimer threshold level can be used to define a negative test that safely excludes PE and reduces the use of imaging. However, the utility of this approach in patients hospitalized for chronic obstructive pulmonary disease (COPD) exacerbation is undefined. Methods We ran an analysis of the patients hospitalized for COPD exacerbation and randomized to the intervention in the SLICE trial. Using the conventional strategy as the reference, we compared the proportion of patients with a negative D-dimer result, and the negative predictive value and sensitivity of three D-dimer threshold strategies for initial PE or subsequent diagnosis of venous thromboembolism (VTE): the age-adjusted strategy, the Wells-adjusted strategy, and the YEARS-adjusted strategy. Results We included 368 patients. Using a conventional threshold, 182 (49.5%) patients had negative D-dimer values, of whom 1 (0.6%) had PE (sensitivity, 94.1%). The use of an age-adjusted threshold increased the number of patients in whom PE could be excluded from 182 to 233 patients (63.3%), and the proportion of false-negative findings increased from 0.5% to 1.7% (sensitivity, 76.5%). With the use of the Wells or YEARS strategies, 64.4% and 71.5% had negative values, and the proportion of false-negative findings was 2.5% (sensitivity, 64.7%) and 2.7% (sensitivity, 58.8%), respectively. Conclusions In patients hospitalized for COPD exacerbation, compared with the conventional strategy, age- or clinically-adjusted strategies of D-dimer interpretation were associated with a larger proportion of patients in whom PE was ruled out with a higher failure rate. Trial Registration ClinicalTrials.gov number: NCT02238639 .